SOCIAL-PSYCHOLOGICAL FACTORS OF ADOLESCENTS’ ADDICTIVE BEHAVIOR TO INTERNET GAMES - Eshnazarova, B. (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This scientific article examines the socio-psychological factors influencing adolescents’ addictive behavior toward internet games. The study analyzes the role of family environment, peer influence, virtual communication, and digital technologies in the development of gaming addiction. Psychological consequences and preventive strategies are also discussed.